Oral Immunization with Cholera Toxin Provides Protection against Campylobacter jejuni in an Adult Mouse Intestinal Colonization Model - Albert, M. John (American Society of Microbiology, 2013)
Immunity to Campylobacter jejuni, a major diarrheal pathogen, is largely Penner serotype specific. For broad protection, a vaccine should be based on a common antigen(s) present in all strains. In our previous study (M. J. Albert, S. Haridas, D. Steer, G. S. Dhaunsi, A. I. Smith, and B. Adler, Infect. Immun. 75:3070–3073, 2007), we demonstrated that antibody to cholera toxin (CT) cross-reacted with the major outer membrane proteins (MOMPs) of all Campylobacter jejuni strains tested. In the current study, we investigated whether immunization with CT protects against intestinal colonization by C. jejuni in an adult mouse model and whether the nontoxic subunit of CT (CT-B) is the portion mediating cross-reaction. Mice were orally immunized with CT and later challenged with C. jejuni strains (48, 75, and 111) of different serotypes. Control animals were immunized with phosphate-buffered saline. Fecal shedding of challenge organisms was studied daily for 9 days. Serum and fecal antibody responses were studied by enzyme-linked immunosorbent assay (ELISA) and immunoblotting. The cross-reactivity of rabbit CT-B antibody to MOMP was studied by immunoblotting. The reactivity of 21 overlapping 30-mer oligopeptides (based on MOMP’s sequence) against rabbit CT antibody was tested by ELISA. Test animals produced antibodies to CT and MMP in serum and feces and showed resistance to colonization, the vaccine efficacies being 49% (for strain 48), 37% (for strain 75), and 34% (for strain 111) (P, ≤0.05 to ≤0.001). One peptide corresponding to a variable region of MOMP showed significant reactivity. CT-B antibody cross-reacted with MOMP. Since CT-B is a component of oral cholera vaccines, it might be possible to control C. jejuni diarrhea with these vaccines.